A randomized trial of the dural puncture epidural technique combined with programmed intermittent epidural boluses for labor analgesia - Wang, Jing; Zhang, Longxin; Zheng, Lihua; Xiao, Peihan; Wang, Yuping; Zhang, Li; Zhou, Min (Annals of palliative medicine, 2021)
Continuous epidural infusion (CEI) can provide analgesia during labor. The dural puncture epidural (DPE) technique is used to accelerate the onset of neuraxia anesthesia. The primary objective of this study was to compare the percentage of patients that received adequate labor analgesia following an injection of 0.08% epidural ropivacaine via the DPE and CEI techniques combined with the PIEB mode of maintenance. Patients who were laboring were randomly allocated to receive either CEI + PIEB or DPE + PIEB. Subjects indicated a VAS score immediately prior to epidural placement, and parturients with a VAS score of ≤50 mm were excluded. A 25-gauge needle was used for dural puncture. Analgesia was provided with 10 mL of 0.08% ropivacaine and 0.4 μg/mL of sufentanil, and was maintained at 10 mL/h in both groups with the same solution. All pumps were programmed for patient-controlled epidural analgesia (PCEA) boluses of 5 mL with a 20-minute lockout. VAS measurements were collected at 2-minute intervals for up to 20 minutes after initiation of the epidural bolus. The median time to adequate analgesia was analyzed using Kaplan-Meier curves and Cox proportional hazard models. Data were collected and analyzed from 200 participants (n=100 per group). Adequate analgesia at 10 minutes was higher in the DPE + PIEB group compared to the CEI + PIEB group (DPE + PIEB =58.4% vs. CEI + PIEB =41.6%; P=0.007). The DPE + PIEB group also had a shorter median time to adequate analgesia [median (95% confidence interval (CI), 8 minutes (7-9 minutes) vs. 12 minutes (10-14 minutes)] compared to the CEI + PIEB group [hazard ratio (HR) =1.488; 95% CI, 1.105-2.002; P=0.002]. The percentage of parturients with adequate analgesia at 10 minutes was higher with DPE + PIEB compared to CEI + PIEB. Furthermore, the DPE + PIEB mode was associated with a faster time to a VAS score ≤30 mm.